Assays for Chemotaxis and Chemoattractant-Stimulated TorC2 Activation and PKB Substrate Phosphorylation in Dictyostelium - Kamimura, Yoichiro (Methods Mol Biol, 2009)
Chemotaxis is a highly coordinated biological system where chemoattractants trigger multiple signal transduction pathways which act in concert to bring about directed migration. A signaling pathway acting through PIP(3), which accumulates at the leading edge of the cell, has been extensively characterized. However, chemotaxis still remains in cells depleted of PIP(3), suggesting there are PIP(3)-independent pathways. We have identified a pathway involving TorC2-PKBR1 as well as another containing PLA2 activity that act in parallel with PIP(3). Activation of PKBR1, a myristoylated Protein Kinase B homolog, is dependent on TorC2 (Rapamycin-insensitive Tor complex 2) kinase but is completely independent of PIP(3). In response to chemoattractant, PKBs rapidly phosphorylate at least eight proteins, including Talin B, PI4P 5-kinase, two RasGefs, and a RhoGap. These studies help to link the signaling pathways to specific effectors and provide a more complete understanding of chemotaxis.